Respuesta :

Space

Answer:

y = -1

Step-by-step explanation:

Step 1: Write equation

2(y + 2) - y = 3(y - 1) + 9

Step 2: Solve for y

  1. Distribute: 2y + 4 - y = 3y - 3 + 9
  2. Combine like terms: y + 4 = 3y + 6
  3. Subtract y on both sides: 4 = 2y + 6
  4. Subtract 6 on both sides: -2 = 2y
  5. Divide both sides by 2: -1 = y
  6. Rewrite: y = -1

Step 3: Check

Plug in y to verify it's a solution.

2(-1 + 2) - (-1) = 3(-1 - 1) + 9

2(1) + 1 = 3(-2) + 9

2 + 1 = -6 + 9

3 = 3

ACCESS MORE